Effect of irradiated pork on physicochemical properties of meat emulsions. (February 2016) - Choi, Yun-Sang; Sung, Jung-Min; Jeong, Tae-Jun; Hwang, Ko-Eun; Song, Dong-Heon; Ham, Youn-Kyung; Kim, Hyun-Wook; Kim, Young-Boong; Kim, Cheon-Jei
Abstract: The effect of pork irradiated with doses up to 10 kGy on meat emulsions formulated with carboxy methyl cellulose (CMC) was investigated. Raw pork was vacuums packaged at a thickness of 2.0 cm and irradiated by X-ray linear accelerator (15 kW, 5 MeV). The emulsion had higher lightness, myofibrillar protein solubility, total protein solubility, and apparent viscosity with increasing doses, whereas cooking loss, total expressible fluid separation, and hardness decreased. There were no significant differences in fat separation, sarcoplasmic protein solubility, springiness, and cohesiveness. Our results indicated that it is treatment by ionizing radiation which causes the effects the physicochemical properties of the final raw meat product. Highlights: Effect of irradiation on meat emulsions with cellulose. Pork irradiated with doses up to 10 kGy on meat emulsion. Irradiated pork provided technological advantages.